GRAF DIVISOR CORDIAL - Deasy Bunga Agustina; Bambang Irawanto (MATEMATIKA FSM, UNDIP, 2013)
ABSTRACT.A Let G = (V, E) be a graph and bijection map f:V → 1,2,..| V |. For every edge uv∈E assign the label 1 if either f(u) divide out of f(v) or f(v) divide out of f(u) and assign the label 0 otherwise. A mapping f is called divisor cordial labeling if the difference between the number of edges having labels 0 and the number of edges having labels 1 which is to equal or less one. A graph has a divisor cordial labeling is called divisor cordial graph. Some special classes of graphs such as full binary tree graph, G*K_(2,n) graph, G*K_(3,n) graph where n even, G=<K_(1,n)^((1)),K_(1,n)^((2))> graph, G=<K_(1,n)^((1)),K_(1,n)^((2)),K_(1,n)^((3))> graph and sun graph〖 C〗_(n ) (〖.K〗_1 ) ̅ are divisor cordial.Keywords : divisor cordial labeling, full binary tree graph, G*K_(2,n) graph, G*K_(3,n) graph, G=<K_(1,n)^((1)),K_(1,n)^((2))> graph, G=<K_(1,n)^((1)),K_(1,n)^((2)),K_(1,n)^((3))> graph and sun graph